1999
DOI: 10.1159/000027683
|View full text |Cite
|
Sign up to set email alerts
|

New Approach for 3D Imaging and Geometry Modeling of the Human Inner Ear

Abstract: Obtaining high-resolution three-dimensional (3D) geometry data performs a necessary assumption for modeling cochlear mechanics. Preferably this procedure has to be done noninvasively to preserve the original morphology. Depending on the actual application, various levels of spatial resolution and tissue differentiation should be reached. Here a new approach is presented which allows 3D imaging of temporal bone specimens with intact regions of interest and spatial resolution currently in the 10-μm range, but pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 14 publications
2
35
0
Order By: Relevance
“…The other methods of acquiring digital information from mammals were reported above and include micro CT [15,16] , MRM [17][18][19][20][21] and orthogonal-plane fluorescence optical sectioning microscopy [22] . The image resolutions of micro CT and MRM are still poor in the display of the tiny structures, having a spatial resolution of 10 and 86 m, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other methods of acquiring digital information from mammals were reported above and include micro CT [15,16] , MRM [17][18][19][20][21] and orthogonal-plane fluorescence optical sectioning microscopy [22] . The image resolutions of micro CT and MRM are still poor in the display of the tiny structures, having a spatial resolution of 10 and 86 m, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The capability of most modern clinical high-resolution computed tomography (CT) [10,11] or magnetic resonance imaging [12][13][14] is still quite limited for the three-dimensional reconstruction of membranous compartments. Although micro CT [15,16] and magnetic resonance microscopy (MRM) [17][18][19][20][21] were used for the three-dimensional reconstruction of the mammalian inner ear, their spatial resolution is too limited for any precise three-dimensional reconstruction of the tiny structures of the human inner ear. Those approaches make it possible to acquire a general three-dimensional shape presenting merely the shapes and correlations of the bony labyrinth, the membranous labyrinth and the nerves located in the temporal bone, but not the details of the membranous labyrinth that are of great significance to the VR research of biophysical processes in the inner ear.…”
mentioning
confidence: 99%
“…Microtomography based on x-ray absorption contrast has been used for non-destructive 3D structure determination of human cochleae. 2,[10][11][12] For small scale soft tissues, e.g., within the mouse cochlea, absorption is weak and the interaction with x-rays results predominantly in a shifted phase. Therefore, coherent x-ray methods 8,9,13 exploiting the phase shift induced by the sample are particularly well suited for cochlea imaging, as shown by recent synchrotron studies.…”
mentioning
confidence: 99%
“…High-resolution magnetic resonance microscopy and computer microtomography are powerful tools to study living and preserved tissue (Vogel, 1999). Nuclear magnetic resonance (NMR) studies were reported with a voxel size of 25 lm 3 (Salt et al, 1995;Vogel, 1999) and an intact mammalian cochlea was studied by orthogonalplane fluorescence optical sectioning with a 16-lm 3 voxel size (Voie, 2002). The resolution with these methods is limited when compared to that with light microscopy.…”
Section: Introductionmentioning
confidence: 99%